Positive Regulation of the Antiviral Activity of Interferon-Induced Transmembrane Protein 3 by S-Palmitoylation - Wen, Shubo; Song, Yang; Li, Chang; Jin, Ningyi; Zhai, Jingbo; Lu, Huijun (Frontiers in Immunology, 2022)
The interferon-induced transmembrane protein 3 (IFITM3), a small molecule transmembrane protein induced by interferon, is generally conserved in vertebrates, which can inhibit infection by a diverse range of pathogenic viruses including the influenza virus. However, the precise antiviral mechanisms of IFITM3 remain unclear. At least four post-translational modifications (PTMs) were found to modulate the antiviral effect of IFITM3. These include positive regulation provided by S-palmitoylation of cysteine and negative regulation provided by lysine ubiquitination, lysine methylation, and tyrosine phosphorylation. IFITM3 S-palmitoylation is an enzymatic addition of a 16-carbon fatty acid on the three cysteine residues within or adjacent to its two hydrophobic domains at positions 71, 72, and 105 that is essential for its proper targeting, stability, and function. As S-palmitoylation is the only PTM known to enhance the antiviral activity of IFITM3, enzymes that add this modification may play important roles in IFN-induced immune responses. This study mainly reviews the research progress on the antiviral mechanism of IFITM3, the regulation mechanism of S-palmitoylation modification on its subcellular localization, stability, and function, and the enzymes that mediate the palmitoylation modification of IFITM3, which may help elucidate the mechanism by which this IFN effector restrict virus replication and thus aid in the design of therapeutics targeted at pathogenic viruses